PENINGKATAN KUALITAS SUMBER DAYA MANUSIA (SDM) PARIWISATA MELALUI LEMBAGA PELATIHAN KERJA (LPK) OVERSEAS TRAINING CENTER (OTC) BALI - Santi Santi; I Wayan Eka Mahendra; Francisca Titing Koerniawaty (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this study was to analyze and find out the mechanism of learning or training at the Overseas Training Center (OTC) Bali Job Training Institute (OTC), then to analyze and find out the level of satisfaction of trainees and graduate users who have attended learning at the Job Training Institute (LPK). Overseas Training Center (OTC) Bali, as well as to analyze and find out strategies that can be carried out by the Overseas Training Center (OTC) Bali to be able to improve its training delivery system in accordance with the competencies of Human Resources (HR) requested by the tourism industry in Bali. Collecting data using questionnaires & interviews. The data analysis technique used is descriptive analysis and SWOT analysis. The results of the analysis show that the learning or training mechanism at the Overseas Training Center (OTC) Bali Job Training Institute (OTC) has been running very well according to standards and professionalism in the field of tourism, especially cruise ships and hospitality at the international level, as well as the basis of learning at OTC Bali already based on SKKNI and more dominant practice to industry than theory. There is a very high level of satisfaction from students and graduates who have attended learning at the Overseas Training Center (OTC) Bali Job Training Institute (OTC) Based on the results of the SWOT analysis, the appropriate strategy used by the Bali Overseas Training Center (OTC) is a strategy model SO is a strategy that uses strength (Strength) and by taking advantage of opportunities (Opportunities) that are owned in the industry, namely through increasing product excellence.